2016
DOI: 10.1039/c5fo00987a
|View full text |Cite
|
Sign up to set email alerts
|

The impact of long-term dietary pattern of fecal donor on in vitro fecal fermentation properties of inulin

Abstract: Although the composition of the gut microbiota is of interest, the functionality, or metabolic activity, of the gut microbiota is of equal importance: the gut microbiota can produce either harmful metabolites associated with human disease or beneficial metabolites that protect against disease. The purposes of this study were to determine the associations between dietary intake variables and fecal short and branched chain fatty acid (S/BCFA) concentrations; to determine the associations between dietary intake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…BCFAs are major markers of protein fermentation, which is likely to be detrimental to host health (Yang & Rose, 2015). Calik and Ergun (2015) found that there were no apparent differences in cecal acetate, propionate, butyrate, and total SCFAs, which was consistent with our result.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…BCFAs are major markers of protein fermentation, which is likely to be detrimental to host health (Yang & Rose, 2015). Calik and Ergun (2015) found that there were no apparent differences in cecal acetate, propionate, butyrate, and total SCFAs, which was consistent with our result.…”
Section: Discussionsupporting
confidence: 82%
“…SCFAs have been shown to regulate inflammation, appetite and insulin resistance (Yang & Rose, 2016), which play a significant role in host health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations